What Future for Hahnemann's Therapeutic System? - Hoover, Todd A. (Homeopathy, 2020)
This article explores the historical growth patterns in homeopathy, recent shifts in perception, and a likely future of this type of medicine. Homeopathic medicine developed as a contradictory approach to health compared to the orthodox view of mainstream medicine. Over the past two centuries, this form of health care has maintained its heterodox position under continued attacks from the established order. Modern medicine is being pushed by materialism and the drive to generate profits by large pharmaceutical and health care corporations. Whilst homeopathy has also enjoyed economic growth in many markets around the world, rising popularity of this type of treatment has been shown to generate regulatory concerns on some fronts. Recent pressures from regulatory authorities have resulted in both setbacks and improved situations for homeopathic prescribers, varying by country where they are located. Despite widespread attacks in the press and from some governmental authorities, users of homeopathic therapies remain staunchly attached to this form of treatment. The future of homeopathy will likely continue to be as rocky as it has been for the past two centuries.
Keywords: homeopathy; future; materialism; science; world